The Effect of Competence, Independence, and Professional Auditors to Audit Quality - Lia Dahlia Iryani (UNIVERSITAS PAKUAN, 2017)
Abstract. The objectives to be achieved in this research are as follows: 1. To know the auditor's competence to audit quality, 2. To know the auditors independence to audit quality, 3. To know auditors professionalism to audit quality. This research uses Multiple Linear Regression Analysis with Statistical Package for Social Sciences (SPSS) Ver program.21:00. The subjects of this research are 18 Public Accountant Firm in South Jakarta with the number of respondents as many as 97 respondents. Based on the results of hypothesis testing and refers to the formulation and objectives of this study, it can be drawn conclusions as follows: 1. Competence auditors in carrying out the audit have a positive and significant impact on audit quality at Public Accounting Firm in South Jakarta, so the more competent an auditor The better the quality of the audit, 2. The independence of the auditor in conducting the audit has a positive and significant impact on the quality of audit at the Public Accountant Office in South Jakarta, so the higher the auditor's independence attitude the higher the audit quality, 3. Auditor professionalism in conducting audit has a positive and significant impact on audit quality at Public Accountant Office in South Jakarta, so the higher the auditor's professionalism, the higher the audit quality. Keywords: Competence, Indepedence, Professional, Audit Quality.